2014
DOI: 10.1177/1758573214535574
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of glenosphere design and material on clinical outcomes of reverse total shoulder arthroplasty

Abstract: Background: The aim of this multicentre retrospective study was to compare reverse total shoulder arthroplasty clinical outcomes with glenospheres of different diameters, designs and materials. Methods: Between 2003 and 2008, 133 patients were divided into three groups: 60 (45%) with 36-mm standard CoCrMo (group A), 21 (16%) with 36-mm eccentric cobalt-chromium-molybdenum (CoCrMo) (group B) and 52 (39%) with 44-mm cross-linked ultra-high molecular weight polyethylene (X-UHMWPE) (group C) glenospheres. Mean (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…References 1 , 4 , 5 , 7 , 8 , 9 , 14 , 20 , 25 , 26 , 29 , 30 , 31 , 35 , 37 , 40 , 41 , 42 , 44 , 46 , 47 , 48 , 49 , 51 , 52 , 53 , 54 , 55 , 58 , 61 , 62 , 64 , 66 , 68 , 72 , 73 , 75 , 77 , 78 , 80 , 81 , 83 , 84 , 85 , 87 , 91 , 92 , 93 , 98 , 102 , 103 , 106 , 107 , 108 , 110 , 111 , 113 , 114 , 116 , 117 , 118 , 119 , 123 , 125 , 128 , 131 , 133 , 136 , 137 , 138 ...…”
unclassified
“…References 1 , 4 , 5 , 7 , 8 , 9 , 14 , 20 , 25 , 26 , 29 , 30 , 31 , 35 , 37 , 40 , 41 , 42 , 44 , 46 , 47 , 48 , 49 , 51 , 52 , 53 , 54 , 55 , 58 , 61 , 62 , 64 , 66 , 68 , 72 , 73 , 75 , 77 , 78 , 80 , 81 , 83 , 84 , 85 , 87 , 91 , 92 , 93 , 98 , 102 , 103 , 106 , 107 , 108 , 110 , 111 , 113 , 114 , 116 , 117 , 118 , 119 , 123 , 125 , 128 , 131 , 133 , 136 , 137 , 138 ...…”
unclassified
“…The inversion of conventional bearing materials was recently introduced in reverse total shoulder arthroplasty (rTSA) using an all-polyethylene glenosphere articulating against a metal humeral inlay. [9][10][11] The idea of bearing material inversion was supported by the need to avoid the scapular notching phenomenon. This complication is due to mechanical impingement and abrasion of the polyethylene humeral inlay against the scapular bone, which leads to increased polyethylene debris generation and osteolysis.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Various factors have been reported that are related to the poor improvement of shoulder function after RSA including age, 15 , 18 sex, 15 patients’ stature, 27 obesity, 39 deltoid muscle volume, 43 preoperative range of motion, 14 preoperative diagnosis, 11 , 19 , 42 and glenosphere size and position. 6 , 10 , 30 , 32 , 33 …”
mentioning
confidence: 99%